THE INFLUENCE OF DISCOVERY LEARNING MODELS AND SOLVING SKILLS PROBLEMS WITH PPKn LEARNING OUTCOMES GRADE 4 STUDENTS AT SD KATOLIK DISKI - Putri Melly Andani Marbun; Deny Setiawan; Asih Menanti (Teunuleh Publisher, 2020)
This research is motivated by the purpose of education to obtain good learning outcomes. Such success depends on internal and external factors, as one part of the internal factor is problem solving skills. The existence of problem-solving skills students can more easily overcome problems encountered when learning or designed by teachers. The purpose of this study was to find out the comparison of students' PPKn learning outcomes between the Discovery Learning model and the Think Pair and Share model, also to find out the comparison of PPKn learning outcomes of students who have high problem solving skills with students who have low problem solving skills, and also to know the interaction between the learning model and problem solving skills to the learning outcomes of PPKn students in grade IV of Diski Catholic Elementary School. This study using quantitative approach with the results of the study showed that the results of ppkn students with Discovery Learning model is higher than the learning results of PPKn students with Think Pair and Share model, evidenced from Qhitung > Qtabel (4,344 > 2,814; with a level of 5%). PPKn learning outcomes of students who have high problem-solving skills are higher than ppkn learning outcomes of students who have low problem-solving skills, as evidenced by Qhitung > Qtabel (3,030 > 2,814; with a level of 5%). There is an interaction between learning models and problem-solving skills to students' PPKn learning outcomes, as evidenced by Fhitung > Ftabel which is 8.59 > 4.20. The conclusion of this study explains that the learning outcomes of students who have high and low skills are more suitable to be taught with discovery learning models than students who are taught using the Think Pair Share model.